ABNORMAL RETURN SAHAM TERHADAP PERISTIWA POLITIK DI INDONESIA - Citra Puspa Permata (ICMA Nasional, 2023)
This study aims to examine the difference in the average abnormal return after and before the implementation of the presidential election. This research uses an event study, where research is carried out for 7 working days before to 7 working days after the implementation of the presidential election. This research uses information obtained from the Indonesia Stock Exchange. The information used in this examination includes daily closing costs, LQ45 stock list. Expected return uses a market-adjusted model. While the examples of stocks used are stocks that are included in the LQ45 list on the Indonesia Stock Exchange. The results show that based on statistical tests on the average abnormal return of stocks over a certain period of time, it was found that there was no significant difference between the average abnormal return after and before the implementation of the presidential election.